2021
DOI: 10.3390/nano11030630
|View full text |Cite
|
Sign up to set email alerts
|

Diversified Phenomena in Metal- and Transition-Metal-Adsorbed Graphene Nanoribbons

Abstract: Adatom-adsorbed graphene nanoribbons (GNRs) have gained much attention owing to the tunable electronic and magnetic properties. The metal (Bi, Al)/transition metal (Ti, Fe, Co, Ni) atoms could provide various outermost orbitals for the multi-orbital hybridizations with the out-of-plane π bondings on the carbon honeycomb lattice, which dominate the fundamental properties of chemisorption systems. In this study, the significant similarities and differences among Bi-/Al-/Ti-/Fe-/Co-/Ni-adsorbed GNRs are thoroughl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Likewise, dipole corrections were added along the z direction. The calculations considered the ferromagnetism character of the Fe atoms in which the magnetic moment of partially filled Fe sites rested at ±5.0 µB [27]. A binding energy (E B ) for all studied adsorption configurations of the molecule on the surface were computed using the equation;…”
Section: Computational Detailsmentioning
confidence: 99%
“…Likewise, dipole corrections were added along the z direction. The calculations considered the ferromagnetism character of the Fe atoms in which the magnetic moment of partially filled Fe sites rested at ±5.0 µB [27]. A binding energy (E B ) for all studied adsorption configurations of the molecule on the surface were computed using the equation;…”
Section: Computational Detailsmentioning
confidence: 99%
“…20 The finite-size terminations of 2D graphene create quasi-one-dimensional (1D) derivatives of 2D graphene called graphene nanoribbons (GNRs). The 1D GNRs with a one-atom thickness, 1D quantum confinement, and peculiar edge morphologies have attracted much interest owing to their remarkable properties over their 2D counterparts, 21,22 in which it should be mentioned that the first theoretical prediction of GNRs was done by M. Fujita et al in 1996, 23 while the later experimental synthesis of GNRs was finally realized in 2009. 24,25 In terms of the geometric aspects, 1D GNRs are generated from the finite-size cutting of 2D graphene sheets or the unzipping of carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Although two-dimensional materials exhibit many prime properties, there are still some shortcomings or some aspects that need to be improved, so it is also very important to modulate their properties. Similar to traditional semiconductor engineering, defect design, , adsorption, and doping are mainly used to manipulate the performance of 2D materials. These methods can modify in a large range the electronic structure including the magnetic state. For instance, Singh et al have shown how the magnetic order, the electronic state, and the thermodynamic properties of MoS 2 and WS 2 depend on the doping position of Mn atoms therein .…”
Section: Introductionmentioning
confidence: 99%